ANALYSIS OF THE IMPACT OF CLIMATE CHANGE ON THE TOURISM SECTOR OF ASEAN COUNTRIES IN 2005 - 2019 - Kripsi Alfian; Evi Gravitiani (Journal of Applied Economics in Developing Countries, 2021)
Climate change impacts the tourism sector and affects the economic sector. With climate change, the number of tourist arrivals declined. It also affects the economic sector, especially gross domestic product and per capita income, which is impacted due to a decline in tourism demand. The study aimed to determine the impact of climate change in temperature and rainfall, gross domestic product, and per capita income on the number of tourist arrivals in 10 ASEAN countries in 2005 - 2019 variables. The research method used was panel data analysis with Random Effect Model (REM). This model was chosen as the best model based on the test results in the panel data. This study is a quantitative study with a times series of 2005-2019 and a cross-section of Ten ASEAN Countries. The results of this study indicate that the temperature variable positively affected the number of tourist arrivals. In contrast, the rainfall variable negatively affected the number of tourist arrivals, and gross domestic product and income per capita variables positively affected the number of tourist arrivals. Keywords: Climate Change, Income per capita, Gross domestic product, Random Effect Model